In (visual) search for a new distraction: the efficiency of a novel attentional deployment versus semantic meaning regulation strategies - Sheppes, Gal; Brady, William J.; Samson, Andrea C. (Frontiers in Psychology, 2014)
Cognitive emotion regulation strategies are considered the king’s highway to control affective reactions. Two broad categories of cognitive regulation are attentional deployment and semantic meaning. The basic distinctive feature between these categories is the type of conflict between regulatory and emotional processes for dominance, with an early attentional selection conflict in attentional deployment and a late appraisal selection conflict in semantic meaning. However, prior studies that tested the relative efficacy of these two regulatory categories varied the type and the degree of conflict. Our major goal was to test the relative efficacy of a novel attentional deployment strategy (visual search distraction) and a classic semantic meaning strategy (reappraisal) that have a different type of conflict but a matched degree of conflict. Specifically, visual search distraction involves a strong degree of attentional selection conflict manifested in attending subtle non-emotional features that are camouflaged within potent negative emotional stimuli. Reappraisal involves a strong degree of appraisal selection conflict manifested in construing neutral reappraisals that rely on potent negative emotional appraisals. Based on our theoretical model we hypothesized and found that visual search distraction was as effective as cognitive reappraisal in down-regulating the experience of low intensity of negative emotion (Study 1), but more effective, less effortful, and more strongly blocking emotional information processing than cognitive reappraisal when regulating high intensity (Study 2). A final study ruled out a demand characteristics explanation by showing that participants’ expectations about how they should feel diverged from how they actually reported feeling following regulation (Study 3). Our findings suggest that the basic difference in the type rather than degree of conflict between attentional deployment and semantic meaning determines strategies' outcome.